The International Monetary Fund and the Learning organization : the role of independent evaluation - Schwartz, Moises J.; Rist, Ray C. (Washington, D.C International Monetary Fund (IMF), 2016)
The benefits of independent evaluation in international financial institutions have long been recognized. However, independent evaluation in these organizations is of increased relevance during uncertain times that call for more credible and legitimate institutions. While evaluation has long played a function in the IMF, and its role has expanded substantially with the creation of the IEO, independent evaluation has yet to take on a role within the IMF that fully reflects its potential contribution. A strong global economy requires a strong IMF, and a strong IMF requires a strong independent evaluation culture and practice. The establishment of the IEO was only the start of a process that still needs to be fostered and cultivated. Successful independent evaluation is important for the IMF to be perceived as legitimate and credible-and to achieve it, the independent evaluation function needs to be further integrated in the learning process and culture of the Fund. Independent evaluation has played a significant role in contributing to the improvement of the IMF, but the pending challenge is for the IMF and the IEO to create a shared culture that fully embraces the purpose and mission of the IEO, and the learning opportunities offered by independent evaluation. The IMF's organizational culture has a profound role to play in prompting actions to make learning from independent evaluation a more vibrant element of the Fund's activities. This book calls on IMF management to take a more active role in instilling the positive value of independent evaluation across the organization and thus enabling independent evaluation to bring the IMF closer to what the literature defines as the ideal of a 'learning organization.'
​ 1. Introduction --  2. Independent evaluation at the IMF: A brief history --  3. The institutional role of independent evaluation --  4. Independent evaluation and the tension between accountability and learning --  5. The learning-accountability spectrum in IEO evaluation reports --  6. Friction by design and other structural issues that have hampered independent evaluation at the IMF --  7. Organizational learning, the learning organization, and independent evaluation --  8. Organizational learning: the IMF’s use of new knowledge generated by the IEO --  9. Culture, leadership, and independent evaluation --  10. Conclusion: what is to be done?
Includes bibliographical references (p. 163-166)
Keywords: Banks and Banking; BANKS; FINANCIAL INSTITUTIONS; LEARNING; EVALUATION; IMF; International Monetary Fund. Independent Evaluation Office